Pakistan’s Infrastructure Capital-Growth Analysis - Mazher, Muhammad Ahmad; Dahalan, Jauhari (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This empirical study facet at Pakistan for the period between 1960 and 2017 in the connection between public investment, public capital stock, private investment, private capital stock, and real GDP. Design/Methodology- Using theoretical and empirical literature assessment, to measure the impact of private investment, private capital stock, government investment, and government capital stock on Pakistan's real gross domestic product, we involved the ARDL Bound tests. Findings- A positive and significant connection was revealed between government investment, a private capital stock with real GDP. Private investment showed a substantial but negative impact in the short run, despite capital stocks indicating a positive and insignificant relationship with Pakistan's RGDP. The long-term consequences showed that the government's capital stocks, public investment, private capital stocks, and RGDP from Pakistan are linked positively and significantly. Private investment, however, has shown harmful and detrimental or insignificant relations with Pakistan's RGDP. Practical Implications- Our study may benefit the Pakistani economy, particularly while useful for academics and researchers to understand the basic concept of 'capital-growth' philosophy.